Supportive supervision in improving stress management skills on employees of health social security implementing agency in South Tangerang City - Damayanti, Yulia Herman; Sokhivah, Sokhivah; Hamid, Almisar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Frontline personnel in South Tangerang City serve participants and prospective participants directly and indirectly. Work is pressure-prone. Supportive supervision is needed to reduce employee stress. This study aims to determine the causes of stress for Health Social Security Implementing Agency employees in South Tangerang City, the implementation of supportive supervision to improve employee stress management, and the factors that support and inhibit supportive supervision in improving employee stress management. This research is descriptive and qualitative. Workload, role ambiguity, participant attitudes, individual mental states of employees, and work support facilities cause stress for Health and Social Security Implementing Agency staff in South Tangerang City, according to this study. To reduce employee stress, supportive supervision is used. South Tangerang's Health Social Security Implementing Agency provides emotional, instrumental, appreciating, informational, social integration, and spiritual support. Role play, sharing sessions, and strong work connections enhance supportive supervision in enhancing employee stress management. Participants' attitudes and employees' personalities are difficulties.